N6‐methyladenosine demethylase FTO suppresses clear cell renal cell carcinoma through a novel FTO‐PGC‐1α signalling axis. Issue 3 (16th January 2019) - Zhuang, Changshui; Zhuang, Chengle; Luo, Xiaomin; Huang, Xinbo; Yao, Lv; Li, Jianfa; Li, Yawen; Xiong, Tiefu; Ye, Jing; Zhang, Fangting; Gui, Yaoting
Abstract: The abundant and reversible N6‐methyladenosine (m6A) RNA modification and its modulators have important roles in regulating various gene expression and biological processes. Here, we demonstrate that fat mass and obesity associated (FTO), as an m6A demethylase, plays a critical anti‐tumorigenic role in clear cell renal cell carcinoma (ccRCC). FTO is suppressed in ccRCC tissue. The low expression of FTO in human ccRCC correlates with increased tumour severity and poor patient survival. The Von Hippel‐Lindau‐deficient cells expressing FTO restores mitochondrial activity, induces oxidative stress and ROS production and shows impaired tumour growth, through increasing expression of PGC‐1α by reducing m6A levels in its mRNA transcripts. Our work demonstrates the functional importance of the m6A methylation and its modulator, and uncovers a critical FTO‐PGC‐1α axis for developing effective therapeutic strategies in the treatment of ccRCC.